Analysis of Science Textbooks for Instructional Effectiveness - Khine, Myint (Springer, 2013)
Science educators unanimously agree that textbooks play an important role in teaching and learning process (Clement, 2008; Koppal & Caldwell, 2004). For this reason, numerous research studies have been conducted in science textbook analysis in the past several decades. In 1941, Graham noted that “The textbook is an old instrument in learning and teaching processes” and traced the origin of the textbook that can be dated back to the Greek classical era. With the invention of the printing press, textbooks became omnipresent in every school. Since the textbooks are being used as a major source of information in teaching a particular subject, the quality and accuracy of the content is crucial for their educational effectiveness.